Adverse events following Synflorix vaccination reported to the Vaccine Adverse Event Reporting System (VAERS), 2010–2024 - Lingyun Cui; Nian Tong; Sicong Hou; Chun Yu (PLoS ONE, 2026)
Background Synflorix is a conjugate vaccine targeting Streptococcus pneumoniae, effectively reducing pneumonia and invasive pneumococcal disease in children under five. To evaluate its safety profile, this study analyzed adverse event (AE) reports associated with Synflorix vaccination submitted to the Vaccine Adverse Event Reporting System (VAERS) from 2010 to 2024. Methods We conducted a retrospective analysis of 1,704 VAERS reports from January 1, 2010, to December 30, 2024. Data processing and statistical analysis were performed using R software. Reporting Odds Ratios (ROR) with 95% confidence intervals (CI) were calculated to identify potential safety signals. Symptom types, onset times, and severity differences across age groups were examined. To facilitate comparison with other vaccines in the VAERS database, certain Preferred Terms (PTs) were normalized per 100,000 reports. Results The most common adverse reactions included crying, pyrexia, hypotonic-hyporesponsive episodes (HHE), pallor, and diarrhea. Newly detected signals not previously listed in the product insert were HHE, hypotonia, pallor, and bronchiolitis. Severe reactions such as pyrexia, crying, vomiting, and pallor showed delayed onset compared to non-severe cases. Infants and toddlers demonstrated stronger systemic reactions within one day post-vaccination, while children aged 2–10 years mostly developed injection site nodules. Adults predominantly experienced localized reactions within 10 days. Reports for elderly individuals (≥55 years) were limited and primarily described mild symptoms like erythema and pyrexia. When compared to other pneumococcal vaccines (PCV7, PCV13, PCV15, PCV20, PPSV23), Synflorix showed the third-highest frequency of mortality and significantly higher RORs for HHE, hypotonia, pallor, and bronchiolitis. Additionally, in terms of the timing of AEs, Synflorix exhibited a similar trend to these vaccines, with reactions primarily occurring in the short-term post-vaccination period. Conclusion Age-specific patterns of adverse events following Synflorix vaccination were observed, with infants and toddlers showing higher intensities of systemic reactions. Compared to other pneumococcal vaccines, Synflorix exhibited a relative higher mortality reporting frequency, along with higher frequencies and RORs for specific PTs, including HHE, hypotonia, pallor, and bronchiolitis. Enhanced post-vaccination monitoring is recommended for younger populations due to their immature immune systems. Age-stratified surveillance can help optimize vaccine safety and management.